Early childhood development under son preference in Vietnam: The role of child gender and birth order - Truc Thi Thanh Nguyen; Wiraporn Pothisiri (PLOS Global Public Health, 2026)
Vietnam has experienced more than two decades of elevated prenatal sex selection due to persistent son preference, yet little is known about whether gender disparities emerge among surviving children in early childhood. This study examines gender differences in early childhood development (ECD) among Vietnamese children aged 24–59 months and investigates whether birth order and family context – key markers of son preference – moderate these differences. Using nationally representative data from the 2020–2021 Vietnam Multiple Indicator Cluster Survey, ECD was assessed across health, learning, and psychosocial domains – using the UNICEF framework. Multivariate logistic regression models were estimated and adjusted for child, mother, home, and household characteristics, including interaction terms to test moderating effects. Among 2,354 children, 21.3% were developmentally off track. Overall, no gender differences in ECD were observed. However, gender disparities emerged when birth order was considered: firstborn daughters had the highest developmental probabilities, whereas firstborn sons had the lowest. These patterns likely reflect a combination of selection into less son-preferring families, differences in biological susceptibility, and gendered parental investment shaped by cultural expectations. Other significant predictors of positive ECD included the absence of functional difficulties, higher maternal education, greater household wealth, access to children’s books, and greater family engagement in stimulating activities. Vietnam provides a unique context in which strong prenatal son preference coexists with largely neutral gender outcomes in early childhood. Nonetheless, birth-order-specific gender patterns highlight the importance of family dynamics in shaping developmental opportunities. Continued monitoring is needed to assess whether gender disparities may emerge as fertility further declines and family structure evolves.